ADJEKTIVA DENOMINAL DALAM BAHASA JAWA - Sumadi, Sumadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This articles investigates the forms and meanings of denominal adjectives in Javanese, especially those derived through affixation. A qualitative-descriptive method was adopted in the data analysis. The results show that denominal adjectives in Javanese can take the forms of N-D. mi-D. -um-D. D-an, D-en, and N-D-i. Each form expresses a particular meaning. Some derived adjectives express the meaning of 'having characteristics of D', some express the meaning of 'being in the state of D', and others the meaning of 'having or being affected by D'.